Traumatic Events and Substance Use Disorders in Adolescents - Basedow, Lukas A.; Kuitunen-Paul, Sören; Roessner, Veit; Golub, Yulia (Frontiers in Psychiatry, 2020)
Objectives Adolescents with substance use disorders (SUD) frequently report traumatic events (TEs) and symptoms of post-traumatic stress disorder (PTSD). This study aimed to assess whether lifetime prevalence rates of TEs and PTSD are related to SUD severity in adolescent psychiatric patients. Methods We analyzed N = 114 self-reports of treatment-seeking German adolescents aged 12 to 18 years, who visited a specialized SUD outpatient unit. Standardized questionnaires were applied to assess SUD severity, the number of TEs and DSM-IV PTSD criteria. Results Patients fulfilling PTSD criteria (28% of the total sample) had a higher Drug Use Disorders Identification Test (DUDIT) score compared to non-PTSD patients with TEs (p <.001), and compared to adolescents without TEs or PTSD (p = .003). Additionally, SUD severity was positively associated with the number of TEs and the number of intrusion, hyperarousal, and avoidance symptoms (all r = .33 to.48, all p <.01). Discussion Adolescent patients with SUD reported 3-times higher rates of TEs, and a 5-time higher prevalence of PTSD following TEs, than the general adolescent population. Adolescent SUD patients with PTSD reported more severe substance use problems than patients without PTSD—regardless of previous TEs. Longitudinal studies are needed in order to investigate the temporal relationship between TEs, PTSD and SUD.